2011
DOI: 10.1063/1.3658813
|View full text |Cite
|
Sign up to set email alerts
|

Structure, electrical and magnetic property investigations on dense Fe-doped hexagonal BaTiO3

Abstract: Hexagonal Ba(Ti 1Àx Fe x )O 3Àd (x ¼ 1/6, 1/3) ceramics treated with post annealing are specifically synthesized to explore the origin mechanism of the unusual ferromagnetism in the doped system. X-ray diffraction refinements and transmission electron microscope experiments reveal that their structures are incommensurately modulated owing to simultaneous oxygen vacancies at both O1 and O2 sites. Consequently, coexisting weak ferrielectricity and weak ferromagnetism are presented at room temperature. Analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 23 publications
5
39
0
Order By: Relevance
“…This phenomenon is well known in transition metal-doped wide band gap ferroelectric materials such as Fe-doped Bi 0.5 Na 0.5 TiO 3 or PbTiO 3 , etc., which results from the contribution of paramagnetic isolated magnetic ion. 9,10,15,16) Thus, the observed magnetism in Ni-doped Bi 0.5 K 0.5 TiO 3 samples is attributed to the competition between ferromagnetism and paramagnetism. For higher Ni-doped Bi 0.5 K 0.5 TiO 3 samples, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon is well known in transition metal-doped wide band gap ferroelectric materials such as Fe-doped Bi 0.5 Na 0.5 TiO 3 or PbTiO 3 , etc., which results from the contribution of paramagnetic isolated magnetic ion. 9,10,15,16) Thus, the observed magnetism in Ni-doped Bi 0.5 K 0.5 TiO 3 samples is attributed to the competition between ferromagnetism and paramagnetism. For higher Ni-doped Bi 0.5 K 0.5 TiO 3 samples, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction peak shifted due to transition metal presence at Ti-site and different ionic radii between them. 9,10,16,17) Note that the ionic radius of Ni depends on the coordination number charge and spin states, etc. The ionic radii of Ni 2+ , Ni 3+ , Ni 4+ and Ti 4+ with six coordination are 0.069, 0.056, 0.048, and 0.061 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations such as X-ray diffraction (XRD), electron paramagnetic resonance (EPR), and Mössbauer spectra have revealed that oxygen vacancies (Vos) prefer to occupy the O1 site and partial Ti 4+ ions will be reduced into Ti 3+ ions in the hexagonal matrix. [9][10][11][12][13][14] The conductivity almost increases linearly with the increase of the oxygen vacancy content since more compensated electrons are introduced at the same time. However, positive contribution of more vacancy to FM only works as the doping content of Fe is less than 12 mol%, 11,15 further doping would weaken the ferromagnetic interaction.…”
Section: Introductionmentioning
confidence: 91%
“…Such a behavior can mainly be ascribed to the crystal and electronic structure changes because of doping, e.g., occupancy ratio change of the dopants at Ti1 and Ti2 sites, the coordination number change of the transition metals and the introduction of defect structures. 10,16 a Author to whom correspondence should be addressed: Electronic mail: rcyu@aphy.iphy.ac.cn. Our previous study on dense Fe-doped hexagonal BaTiO 3 reported the multiferroic behavior of the incommensurately modulated system.…”
Section: Introductionmentioning
confidence: 99%